Project-Based Learning on Respiration Material in Developing Students’ Habits of Mind and Concept Acquisition - Senjayani, Ismi; Retnowati, Rita; Prasetyorini, Prasetyorini (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
This research aims to indentify the development of habits of mind and concept acquisiton through projectbased learning. The data acquired in this research is based on quantitative quasi experiment in which thesamples are not purposely random. The design for data calculation is anon equivalent control group thatconsists of pretest and posttest before and after the treatment in each class. The research takes place atSMAN 1 Cisarua in Eleventh Science academic year 2018/2019 with respiration system as material. Thedevelopment of students’ concept acquisiton and habits of mind in respiration system appears to increaseafter the project based learning program. The result shows there are increase of concept acquisiton to59.45% and increase of habits of mind to about 42.72%. Therefore the project based learning model isincreasing concept acquisition and habits of mind stated in the medium catagory using Gain test. Onesuitable learning model to implement the curriculum is a project based learning